(3fRgI GdeLGdS hefJNH GdfaGFS Yf CNHGQ GdUGdMjfs - (3GdUahQj, YHO GdQMef Hf YHO GdSdGe Hf YHO GdQMef, J(B894(3g`s
(3ChdgG (B:s
(3bGd CHh gQjQI YHO GdQMef GdUahQj bU dfG ef BjGJg YLHG hChQOfG HJhajbg EQTGOG hEYQHG hLYd GdaQbGf CeG HYO aEf Edi GdbUU GdedGM hBNQ CNHGQ Cgd GdUdGM aCLHJgeG Edi ebUhOgeGs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3YGeI ef GdedGFcI hGdEfS hGdLf hChd HTGQ GdGTjGA GdMGUdI aj GdSehGJ hGdCQVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 310s
(3eYLe GdeDdajf(B: 2 / 93s
(3cTa GdXfhf(B: 2 / 1947s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs